A Critical Review on Bring Your Own Device Concept - R.K.A.R. Kariapper (International Journal of Advanced Science and Technology, 2019)
Bring Your Own Device (BYOD) approach allows employees to bring their own devices for work-related purposes. It has been employed in the medical field, higher education, and healthcare sectors. The benefits of this approach are: lower procurement costs, greater workplace flexibility, higher job satisfaction, a more empowered working environment, better productivity, and reduced working hours. The adoption of new technologies or concepts often comes with its pros and cons. Technology is beneficial when proper guidelines are followed. This study performs a systemic literature review by adopting proper and standard guidelines. More than 100 papers from various digital libraries were searched, selected, and filtered. This study concluded with many standard rules, which help utilize the BYOD in a different domain without fail.